Climate change introduces threatened killer whale populations and conservation challenges to the Arctic - Colin J. Garroway; Evelien de Greef; Kyle J. Lefort; Matt J. Thorstensen; Andrew D. Foote; Cory J. D. Matthews; Jeff W. Higdon; Caila E. Kucheravy; Stephen D. Petersen; Aqqalu Rosing‐Asvid; Fernando Ugarte; Rune Dietz; et al. (Global Change Biology, 2024)
The Arctic is the fastest‐warming region on the planet, and the lengthening ice‐free season is opening Arctic waters to sub‐Arctic species such as the killer whale ( Orcinus orca ). As apex predators, killer whales can cause significant ecosystem‐scale changes. Setting conservation priorities for killer whales and their Arctic prey species requires knowledge of their evolutionary history and demographic trajectory. Using whole‐genome resequencing of 24 killer whales sampled in the northwest Atlantic, we first explored the population structure and demographic history of Arctic killer whales. To better understand the broader geographic relationship of these Arctic killer whales to other populations, we compared them to a globally sampled dataset. Finally, we assessed threats to Arctic killer whales due to anthropogenic harvest by reviewing the peer‐reviewed and gray literature. We found that there are two highly genetically distinct, non‐interbreeding populations of killer whales using the eastern Canadian Arctic. These populations appear to be as genetically different from each other as are ecotypes described elsewhere in the killer whale range; however, our data cannot speak to ecological differences between these populations. One population is newly identified as globally genetically distinct, and the second is genetically similar to individuals sampled from Greenland. The effective sizes of both populations recently declined, and both appear vulnerable to inbreeding and reduced adaptive potential. Our survey of human‐caused mortalities suggests that harvest poses an ongoing threat to both populations. The dynamic Arctic environment complicates conservation and management efforts, with killer whales adding top‐down pressure on Arctic food webs crucial to northern communities' social and economic well‐being. While killer whales represent a conservation priority, they also complicate decisions surrounding wildlife conservation and resource management in the Arctic amid the effects of climate change.

Current status of intra-cranial stereotactic radiotherapy and stereotactic radiosurgery in Australia and New Zealand: key considerations from a workshop and surveys - Lauren Pudsey; Annette Haworth; Paul White; Zoe Moutrie; Benjamin Jonker; Matthew Foote; Joel Poder (Physical and Engineering Sciences in Medicine, 2022)
Recently, there has been increased interest worldwide in the use of conventional linear accelerator (linac)-based systems for delivery of stereotactic radiosurgery/radiotherapy (SRS/SRT) contrasting with historical delivery in specialised clinics with dedicated equipment. In order to gain an understanding and define the current status of SRS/SRT delivery in Australia and New Zealand (ANZ) we conducted surveys and provided a single-day workshop. Prior to the workshop ANZ medical physicists were invited to complete two surveys: a departmental survey regarding SRS/SRT practises and equipment; and an individual survey regarding opinions on current and future SRS/SRT practices. At the workshop conclusion, attendees completed a second opinion-based survey. Workshop discussion and survey data were utilised to identify areas of consensus, and areas where a community consensus was unclear. The workshop was held on the 8th Sept 2020 virtually due to pandemic-related travel restrictions and was attended by 238 radiation oncology medical physicists from 39 departments. The departmental survey received 32 responses; a further 89 and 142 responses were received to the pre-workshop and post-workshop surveys respectively. Workshop discussion indicated a consensus that for a department to offer an SRS/SRT service, a minimum case load should be considered depending on availability of training, peer-review, resources and equipment. It was suggested this service may be limited to brain metastases only, with less common indications reserved for departments with comprehensive SRS/SRT programs. Whilst most centres showed consensus with treatment delivery techniques and image guidance, opinions varied on the minimum target diameter and treatment margin that should be applied.

Killer whale genomes reveal a complex history of recurrent admixture and vicariance - Andrew D. Foote; Michael D. Martin; Marie Louis; George Pacheco; Kelly M. Robertson; Mikkel‐Holger S. Sinding; Ana R. Amaral; Robin W. Baird; Charles Scott Baker; Lisa Ballance; Jay Barlow; Andrew Brownlow; et al. (Molecular Ecology, 2019)
Reconstruction of the demographic and evolutionary history of populations assuming a consensus tree‐like relationship can mask more complex scenarios, which are prevalent in nature. An emerging genomic toolset, which has been most comprehensively harnessed in the reconstruction of human evolutionary history, enables molecular ecologists to elucidate complex population histories. Killer whales have limited extrinsic barriers to dispersal and have radiated globally, and are therefore a good candidate model for the application of such tools. Here, we analyse a global data set of killer whale genomes in a rare attempt to elucidate global population structure in a nonhuman species. We identify a pattern of genetic homogenisation at lower latitudes and the greatest differentiation at high latitudes, even between currently sympatric lineages. The processes underlying the major axis of structure include high drift at the edge of species' range, likely associated with founder effects and allelic surfing during postglacial range expansion. Divergence between Antarctic and non‐Antarctic lineages is further driven by ancestry segments with up to four‐fold older coalescence time than the genome‐wide average; relicts of a previous vicariance during an earlier glacial cycle. Our study further underpins that episodic gene flow is ubiquitous in natural populations, and can occur across great distances and after substantial periods of isolation between populations. Thus, understanding the evolutionary history of a species requires comprehensive geographic sampling and genome‐wide data to sample the variation in ancestry within individuals.

Treatment of brain oligometastases with hypofractionated stereotactic radiotherapy utilising volumetric modulated arc therapy - Jeremy Croker; Benjamin Chua; Anne Bernard; Maryse Allon; Matthew Foote (Clinical & Experimental Metastasis, 2016)

Melanoma brain metastases: the impact of nodal disease - James E. Jackson; Bryan H. Burmeister; Elizabeth A. Burmeister; Matthew C. Foote; Janine M. Thomas; Janelle A. Meakin; B. Mark Smithers (Clinical & Experimental Metastasis, 2014)

Monitoring and Assessment of Wetland Condition Using Plant Morphologic and Physiologic Indicators - Federico P. O. Mollard; A. Lee Foote; Matthew J. Wilson; Varina Crisfield; Suzanne E. Bayley (Wetlands, 2013)

College and University Environmental Programs as a Policy Problem (Part 1): Integrating Knowledge, Education, and Action for a Better World? - Susan G. Clark; Murray B. Rutherford; Matthew R. Auer; David N. Cherney; Richard L. Wallace; David J. Mattson; Douglas A. Clark; Lee Foote; Naomi Krogman; Peter Wilshusen; Toddi Steelman (Environmental Management, 2011)

College and University Environmental Programs as a Policy Problem (Part 2): Strategies for Improvement - Susan G. Clark; Murray B. Rutherford; Matthew R. Auer; David N. Cherney; Richard L. Wallace; David J. Mattson; Douglas A. Clark; Lee Foote; Naomi Krogman; Peter Wilshusen; Toddi Steelman (Environmental Management, 2011)